2002
DOI: 10.1159/000065890
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Reduces Neurological Damage in Asphyxiated Newborn Infants

Abstract: Background: Perinatal asphyxia remains one of the most devastating neurologic processes. There is experimental and clinical evidence that cerebral cooling may suppress the biochemical cascades leading to delayed cerebral damage. Objective: To determine if hypothermia started soon after delivery reduces cerebral damage in term infants. Design/Methods: Retrospective chart analysis with historical controls. Ten asphyxiated newborns treated with hypothermia between October 1998 and October 1999 were compared to 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 29 publications
0
25
0
4
Order By: Relevance
“…[131][132][133] Although none of these studies were powered or designed to evaluate neurological outcome, there is some suggestion of improved outcomes. 127,134,135 For example, in a controlled study of head cooling among infants with early stage 2 or 3 encephalopathy, mild systemic hypothermia was associated with a trend to reduced cerebral palsy in survivors (odds ratio 0.46 [0.08, 2.56] vs normothermia). 127 A retrospective study of whole body cooling to between 32 and 34°C in 10 infants found a significant reduction of major neurologic abnormalities and abnormal MRI findings at follow-up compared with 11 historical controls.…”
Section: Phase I and Ii Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[131][132][133] Although none of these studies were powered or designed to evaluate neurological outcome, there is some suggestion of improved outcomes. 127,134,135 For example, in a controlled study of head cooling among infants with early stage 2 or 3 encephalopathy, mild systemic hypothermia was associated with a trend to reduced cerebral palsy in survivors (odds ratio 0.46 [0.08, 2.56] vs normothermia). 127 A retrospective study of whole body cooling to between 32 and 34°C in 10 infants found a significant reduction of major neurologic abnormalities and abnormal MRI findings at follow-up compared with 11 historical controls.…”
Section: Phase I and Ii Studiesmentioning
confidence: 99%
“…127 A retrospective study of whole body cooling to between 32 and 34°C in 10 infants found a significant reduction of major neurologic abnormalities and abnormal MRI findings at follow-up compared with 11 historical controls. 134 A larger randomized pilot study of head cooling with mild hypothermia compared to normothermia found a significant reduction in neuron specific enolase (NSE) levels in cerebral spinal fluid with cooling but only a small increase in normal developmental outcome at 6 months of age in 18 of 23 cooled patients (78.3 %) compared with 19 of 27 (70.4 %) normothermic infants. 135 Finally, a large phase II randomized clinical trial of 65 infants has been reported, in which body cooling to a rectal temperature of 33°C for 48 hours was initiated within 6 hours of birth.…”
Section: Phase I and Ii Studiesmentioning
confidence: 99%
“…Uttalelsen bygger på forskning gjort på voksne og nyfødte, som viser at hypotermibehandling med temperatur mellom 32-34°C gir få bivirkninger. Ingen spesifikk protokoll anbefales, men de europeiske retningslinjene sier at det muligens kan øke antall overlevende barn uten nevrologiske skader (10)(11)(12). Den amerikanske hjerteforeningens retningslinjer for akutt hjerte-lungeredning av barn og nyfødte uttrykker at hypotermibehandling kan vurderes til barn som fortsatt er komatøse etter resuscitering (13).…”
Section: Mangler Forskningunclassified
“…Denne ioneforflytningen fører til at vann følger med inn i cellene. Resultatet er at både cellene og vevet mellom cellene sveller (11,23). Undersøkelser under elektronmikroskop viser at den mest strukturelle skaden i hjernen skjer under denne fasen.…”
Section: Reperfusjonunclassified
“…Eine zentrale Hypothermie (32-34°C) kann von Vorteil sein, während Fieber für das geschä-digte Gehirn nachteilig ist. Eine milde Hypothermie ist ein etabliertes und sicheres Verfahren bei Erwachsenen [361,362] und Neugeborenen [363,364,365,366,367,368]. Obwohl sie das neurologische Outcome von Kindern verbessern kann, wird die therapeutische Hypothermie nach kindlichem Kreislaufstillstand gemäß einer Beobachtungsstudie weder empfohlen noch abgelehnt [369].…”
Section: Kontrolle Und Management Der Körpertemperaturunclassified